Australian managers' experience of global human rights issues - Pedigo, Kerry; Marshall, Verena (Emerald Group Publishing Ltd., 2011)
Purpose – The purpose of this paper is to explore the experiences of Australian managers in relation to human rights issues and corporate responsibility inherent in their international business operations. Design/methodology/approach – The paper reports findings from a qualitative research study; data were gathered from 70 face-to-face interviews with managers in the mining, textile and information technology industries who conducted international operations. The research method used was the critical incident technique, allowing interviewees to recall their observations and anecdotes in dealing with their perceived ethical dilemmas when operating offshore.Findings – Human rights issues represented a serious dilemma for the Australian managers participating in this research. Findings in this study suggest that such issues, and resultant perceived dilemmas around their management, included child labour, hazardous working conditions, discrimination and exploitation of workers. The issues present self-reported major dilemmas for managers as they challenge human rights concepts that underline their own ethical values in relation to the treatment of others in work environments. Respondents in this study report perceived limitations in dealing with cross-cultural ethical issues, driven by economic and social reliance on such practices by their international business counterparts. Originality/value – Understanding the nature of problems faced by Australian business managers in confronting perceived breaches of human rights may assist private and public sector organisations, both inside and outside of Australia, working in international environments. The paper reports insights and solutions offered by respondents encountering global human rights issues in the business context.